2009
DOI: 10.1021/jf902726p
|View full text |Cite
|
Sign up to set email alerts
|

Corn Steep Liquor as a Nutrition Adjunct for the Production of Aspergillus niger Lipase and Hydrolysis of Oils Thereof

Abstract: Corn steep liquor (CSL) has been used as a nutrition adjunct for the production of an extracellular lipase from Aspergillus niger, which has immense importance as an additive in laundry detergent formulations. A five-level four-factorial central composite design was chosen to determine the optimal medium components with four critical variables, namely, CSL, NH4H2PO4, Na2HPO4, and sesame oil, that were found to be influential for lipase production by the classical one-factor-at-a-time method. The model suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 41 publications
0
24
2
Order By: Relevance
“…In case of castor oil that is rich in hydroxyl fatty acids, YLIP15 showed an unusually high hydrolysis. This is in contrast to most reports that suggest that generally lipases from fungi, such as Aspergillus niger , Rhizopus delemar , Humicola lanigunose , and bacterial origin are able to hydrolyze castor oil .…”
Section: Resultscontrasting
confidence: 99%
“…In case of castor oil that is rich in hydroxyl fatty acids, YLIP15 showed an unusually high hydrolysis. This is in contrast to most reports that suggest that generally lipases from fungi, such as Aspergillus niger , Rhizopus delemar , Humicola lanigunose , and bacterial origin are able to hydrolyze castor oil .…”
Section: Resultscontrasting
confidence: 99%
“…Santos et al [10] reported that the increase in biomass production by C. elegans is due to the presence of considerable amounts of amino acids (alanine, arginine, histidine, leucine, lysine, tyrosine, phenylalanine) and vitamins (biotin, choline, inositol, niacin, pyridoxine, thiamine) that are essential for the growth of the microorganism. Edwinoliver et al [29] also suggest that the use of corn steep liquor for lipase production from Aspergillus niger makes the process green, because this substrate is renewable and economically viable on an industrial scale.…”
Section: Resultsmentioning
confidence: 99%
“…It is also a cheap source of proteins, amino acids, minerals, vitamins, and trace elements and can be used as a rich and effective nutritional substitute for expensive complex media like beef extract, meat extract, yeast extract, and peptone in fermentation studies [12][13][14][15]. Studies have shown that CSL can be used as a nutrition supplement and a cheap nitrogen source for cellular growth in the production of some fermentation products [12,14,16]. Edwinoliver et al [14] showed that the utilization of CSL led to a reduction in the overall cost of lipase production medium by 55-60% of the total medium cost, thereby making the process economically attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CSL can be used as a nutrition supplement and a cheap nitrogen source for cellular growth in the production of some fermentation products [12,14,16]. Edwinoliver et al [14] showed that the utilization of CSL led to a reduction in the overall cost of lipase production medium by 55-60% of the total medium cost, thereby making the process economically attractive. CSL was also shown to be significant out of the ten low-cost media formulated for Clostridium ragsdalei in ethanol production [17].…”
Section: Introductionmentioning
confidence: 99%